2003
DOI: 10.1063/1.1611879
|View full text |Cite
|
Sign up to set email alerts
|

Pinchoff and satellite formation in compound viscous threads

Abstract: The breakup of viscous compound threads in the presence of insoluble surfactant at both interfaces is investigated. We use asymptotic methods in the limit of long axisymmetric waves to derive a coupled system of five one-dimensional ͑1-D͒ partial differential equations governing the evolution of the outer and inner interfaces, the surfactant concentrations there, and the leading order axial velocity component in the jet. The linear, and nonlinear, stability of these equations is then investigated for a wide ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The situation in which a compound jet breaks, on the other hand, is practically important in a number of applications involving microencapsulation. 36 Craster et al 37 have used a onedimensional, long-wave model to analyze the pinch-off dynamics of compound jets. Such models, as their single-fluid counterparts, 9,38,39 assume that the radial velocity is negligible compared to the axial velocity throughout the pinch-off process.…”
Section: Discussionmentioning
confidence: 99%
“…The situation in which a compound jet breaks, on the other hand, is practically important in a number of applications involving microencapsulation. 36 Craster et al 37 have used a onedimensional, long-wave model to analyze the pinch-off dynamics of compound jets. Such models, as their single-fluid counterparts, 9,38,39 assume that the radial velocity is negligible compared to the axial velocity throughout the pinch-off process.…”
Section: Discussionmentioning
confidence: 99%
“…Their algorithm, however, was unable to simulate highly deformed jet shapes due to the use of Lagrangian mesh in which grid points were convected with the fluid velocity. Recently, Craster et al 74 studied the breakup of viscous compound threads of both pure and surfactant-laden liquids using asymptotic methods in the long-wave limit. In this slender-jet analysis, the authors assumed that the axial velocity, to the leading order, was independent of the radial coordinate.…”
Section: Dynamics Of Compound Jetsmentioning
confidence: 99%
“…A wide range of viscosities were investigated and several conclusions (in line with previous work where appropriate) were drawn. It was shown that in the Stokes limit satellites form at breakup even though the surrounding region is a gas -a phenomenon attributed to the electric field since a viscous external shear is required to produce satellites in the non-electrified case (see Lister & Stone (1998), Craster et al (2003), Craster et al (2005)). In addition, the size of the satellite drops was found to increase in the presence of the electric field (also implying that the main drop volume decreases as found by Huebner & Chu (1971) and Magarvey & Outhouse (1962)).…”
Section: Introductionmentioning
confidence: 99%
“…Recent and ongoing analytical studies concentrate on describing the pinching process asymptotically by utilizing the separation of radial and axial scales and mapping the dynamics to a class of self-similar solutions which are universal when inertia is present; notable studies include the work of Eggers (1993), Eggers & Dupont (1994), Papageorgiou (1995), Brenner et al (1996) for jets surrounded by a passive medium; Craster et al (2002), Craster et al (2003), Craster et al (2005), for surfactant-covered or compound jets; Conroy et al (2010), for core-annular arrangements in the presence of electrokinetic effects. Significant computational work has also been carried out with the aim of simulating the phenomena and evaluating the asymptotic theories (the latter are considerably less demanding numerically) -see Newhouse & Pozrikidis (1992), Pozrikidis (1999), Lister & Stone (1998), Sierou & Lister (2003), who simulate Stokes flows using boundary integral methods, and Ambravaneswaran et al (2002), Chen et al (2002), Notz et al (2001), Notz & Basaran (2004), Collins et al (2007), Hameed et al (2008) who compute the flow at arbitrary Reynolds number and in some instances include the effects of surfactants and electric fields -the extensions and novel aspects of the present work are outlined later.…”
Section: Introductionmentioning
confidence: 99%